2022
DOI: 10.3390/su141912109
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Influence between Polyvinyl Chloride (Micro)Plastics and Black Soldier Fly Larvae (Hermetia illucens L.)

Abstract: Due to the expansion in the global population, there is an increase in animal protein demand and waste generation. Currently, food waste derived from supermarkets, etc., which is used to produce biogas, is collected separately and can contain (micro)plastics deriving from food packaging, imposing potential risks to the environment. A possible solution to address protein, waste and plastic concerns can potentially be achieved by rearing black soldier fly (BSF) larvae on such substrates. In this study, we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 51 publications
(84 reference statements)
5
11
0
Order By: Relevance
“…These results are similar to those obtained in other studies investigating the growth performance of BSF larvae reared on substrates containing other microplastics (e.g. polyvinyl chloride, polyethylene or polystyrene) 13,21 . By combining results reported in literature with our results, a hypothesis can be given as to why larval growth was not affected.…”
Section: Bioaccumulation Of Microplasticssupporting
confidence: 90%
See 1 more Smart Citation
“…These results are similar to those obtained in other studies investigating the growth performance of BSF larvae reared on substrates containing other microplastics (e.g. polyvinyl chloride, polyethylene or polystyrene) 13,21 . By combining results reported in literature with our results, a hypothesis can be given as to why larval growth was not affected.…”
Section: Bioaccumulation Of Microplasticssupporting
confidence: 90%
“…In the study of Lievens et al 13 , BSF larvae were exposed to various concentrations of polyvinyl chloride (PVC) macro-, meso-, and microplastics. In general, the presence of PVC in the substrate did not affect the larval growth.…”
mentioning
confidence: 99%
“…The latter can be explained by the fact that sieves are given a nominal mesh size, which might deviate from their actual size. Moreover, Lievens et al (2022) proved that microplastics produced using a cryogenic approach are irregularly shaped [ 18 ]. Hence, the particle-size analysis based on laser diffraction assumes spherical particles in its optical model.…”
Section: Expected Resultsmentioning
confidence: 99%
“…Moreover, Lievens et al (2022) studied the survival effects and bioconversion rate of H. illucens when fed food waste streams containing micro- (<5 mm), meso- (5–25 mm), and macroplastics (>25 mm) present in food packaging material (polyvinyl chloride (PVC)). In contrast to our results, using a different type of plastic, their study showed a complete larval cycle and relatively larger larvae than the control.…”
Section: Discussionmentioning
confidence: 99%
“…H. illucens is one of the most studied insects because of its capacity to convert a wide range of organic wastes. Nevertheless, numerous parameters affect growth performance, complicating comparisons with other studies ( Lievens et al, 2022 ). In the case of plastic conversion, information is still limited and further studies are required to answer multiple unanswered questions regarding plastic degradation mechanisms and bioaccumulation ( Li et al, 2021 ; Beale et al, 2022 ; Mitra & Das, 2022 ).…”
Section: Discussionmentioning
confidence: 99%